A three-dimensional finite element analysis of concrete sleepers and fastening systems subjected to coupling vertical and lateral loads. (April 2021) - El-sayed, H.M.; Zohny, H.N.; Riad, H.S.; Fayed, M.N.
Highlights: A finite element railway track model was executed and rigorously verified. The lateral load path was quantified. The influence of varied lateral to vertical loading ratio was investigated. The local response of concrete sleeper and fastening components was deeply analysed. Abstract: At horizontal railway curves, the rail is typically a subject to both vertical and lateral wheel loads. The underestimated influence of lateral load at such locations in the design process could compromise the structural integrity of the whole railway track system. Rail-seat deterioration and damage of fastening system components are two possible failure mechanisms associated with high lateral loadings that could lead to safety concerns and costly maintenance activities. It is, therefore, of high importance to analyse the track response including concrete sleepers and fastening systems to coupling vertical and lateral loadings. For such end, a three-dimensional finite element railway model was created and subjected to a variety of lateral to vertical loading ratios. Of other elastic fastening systems, the Skl-style (W14) fastening system, which is currently of high demand, was accounted for as a result of it has been barely researched. The finite element model was rigorously verified with the experimental works and classical theories found in the previous knowledge. The finite element outputs could investigate the complex structural behaviour of railway concrete sleepers and fastening systems and the transmission mechanism of the lateral loading through the track system. The findings indicated that the concrete-rail pad interface is significantly influenced by the high lateral to vertical loading ratio which produces localized contact area of high compressive stress; however, the influence of lateral load on the produced stresses of both tension clamps and angled guide plates is minimal. Further, lateral sliding at concrete-rail pad interface was apparent even at low lateral load, increasing the possibility of wear deterioration of the contacting surfaces. Lastly, the gap between the field angled guide plate and the rail base is a critical parameter that influences the lateral load path and failure mechanisms. The outcomes of this research would lead to better insight into the influences of lateral wheel load more clearly and thus contribute to improvements in the current design practices of concrete sleepers and fastening systems at demanding locations.